The economics of producing sustainable aviation fuel: a regional case study in Queensland, Australia. Issue 3 (3rd June 2014) - Hayward, Jennifer A.; O'Connell, Deborah A.; Raison, R. John; Warden, Andrew C.; O'Connor, Michael H.; Murphy, Helen T.; Booth, Trevor H.; Braid, Andrew L.; Crawford, Debbie F.; Herr, Alexander; Jovanovic, Tom; Poole, Michael L.; et al.
Abstract The airline industry has a strong interest in developing sustainable aviation fuels, in order to reduce their exposure to increasing oil prices and cost liability for greenhouse gas emissions. The feasibility and cost of producing sustainable biomass‐based jet fuels at a sufficient scale to materially address these issues is an enormous challenge. This paper builds directly on the biophysical study by H.T. Murphy, D.A. O'Connell, R.J. Raison, A.C. Warden, T.H. Booth, A. Herr, A.L. Braid, D.F. Crawford, J.A. Hayward, T. Javonovic, J.G. McIvor, M.H. O'Connor, M.L. Poole, D. Prestwidge, N. Raisbeck‐Brown & L. Rye, In review, which examined a 25 year scale‐up strategy to produce 5% of projected jet fuel demand in Australia in 2020 (470 mL) in the Fitzroy region of Queensland, Australia. The strategy was based on the use of a mixed ligno‐cellulosic biomass feedstock and assumed, for the sake of exploring and quantifying the scenario, a simplified two‐step conversion process – conversion of biomass to crude bio‐oil within the region, and upgrade to jet fuel at a central Brisbane facility. This paper provides details on the costs of production in this scenario, focusing on two different strategies for biomass utilization, and two types of novel small–medium scale conversion technologies. The cost analyses have taken into account technology learning curves, different economies of scale and key cost sensitivities. The cost of biomass‐based jet fuels is estimated to be between 0.70 and 1.90 L−1 when the efficiency of conversion of biomass to biocrude and subsequently to aviation fuel is varied by ±10% of published values, with an average value of 1.10 L−1. This is within the range of the projected 2035 conventional jet fuel price of 1.50 L−1. Therefore, biomass‐based jet fuel has the potential to contribute to supply of Australia's jet fuel needs in the future.